The Factors and Challenges affecting Digital Economy in Malaysia - Yin Xia Loh; Nor Aziati Abdul Hamid; Choon Sen Seah; Jia Jie Yo; Yu Chung Law; Sze Yin Tan; Hui Loo Chung; Yung Leong Liew; Ching Chong (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
Malaysia is one of the most avid countries in online shopping just behind Indonesia, the largest e-commerce market in ASEAN. In 2020, the Malaysia Digital Economy Corporation’s (MDEC) expectation to hit 20 per cent growth in e-commerce contribution to the digital economy can be achieved as the COVID-19 pandemic has given a huge boost to digital adoption among entrepreneurs. However, many SMEs do not move fast enough to recognize the changing habits and preferences of their consumers. As a result, they do not evolve their business model to adapt to the changes. The purpose of this paper is to conceptually identify and explain the factors and challenges that affecting digital economy in Malaysia.